(untitled) (Journal of the Bangladesh Agricultural University, 2012)
The experiment was conducted in the Agronomy Laboratory of Agrotechnology Discipline, Khulna University, Khulna from 29th August to 17th September, 2009. The experiment was laid out in a Completely Randomized Design (CRD) with two factors and three replications. The aim of the experiment was to study the efficacy of three osmopriming agents viz ., NaCl, KC1 and CaCb with control on seed germination and seedling growth of three T. aman rice varities viz., BRRI dhan40, BRRI dhan41 and BINA dhan7. Among the chemicals CaCb showed best as osmopriming agents and it enhanced all germination parameters. BRRI dhan41 showed the best performance. Better root length and shoot length were observed in control. Seeds of BRRI dhan41 when treated with NaCl showed the highest germination percentage (98.67%), germination energy (88%), germination speed (96.83%), but vigor index (10.63) was found highest in BRRI dhan40 when it was treated with KC1. BRRI dhan41 produced the largest root (8.56 cm) when seeds were treated with NaCl. BRRI dhan40 (10.51 cm) and BINA dhan7 (10.53 cm) produced the highest shoot length at controlled condition and CaCl2 treated seed, respectively. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12013 J. Bangladesh Agril. Univ. 10(1): 1520, 2012